Implementasi Undang-Undang Ketenagakerjaan dan Perjanjian Kerja dalam Ruang Lingkup Hubungan Industrial di V Hotel & Residence - Resya Dwi Marselina; Serlia Ramadhani Putri; Khoirunnisa Idzi (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
The business understanding is one of the foundations of the work relationship that leads to an understanding or lawful relationship for the gatherings leads to freedoms and commitments. With It is trusted that the presence of a work understanding can understand the execution of the freedoms and commitments of representatives parties decently. Nonetheless, practically speaking it has not been completely understood. For get it going, in addition to other things: With government mediation, this is as per the quality of business regulation in Indonesia is that it is blended, in particular both private and public. Aside from that, the standards contained in the work understanding should be as one with every one of the standards contained in the law arrangements, including: The rule of opportunity of agreement, the standard of consensualism, the guideline of assurance regulation, the rule of honest intentions, the guideline of character, the standard of trust, the standard of lawful fairness, the standard of balance, the rule of lawful assurance, the ethical guideline, the standard of fairness and the standard of security. These standards are interconnected with each other, can't be isolated, are applied at the same time, and utilized as a limiting casing for the items in the work understanding.